Expert System to Diagnose Disease Mushroom Plants Using Backward Chaining Method - Dinda Vionica Zahro; Agustina Simangunsong (DISTANCE: Journal of Data Science, Technology, and Computer Science, 2021)
Mushrooms are one of the plants that have high nutritional content that other types of vegetables do not have. This plant is easy to cultivate because it easily adapts to the environment. The risk of loss in the oyster mushroom business cannot be avoided because it is not careful or diligent in maintaining oyster mushrooms. As a tool, an expert system is used to identify the type of oyster mushroom disease using several methods including the backward chaining method. The backward chaining method is a method that starts from the conclusion of several existing facts to refute or support the hypothesis. The results of the research and discussion that have been carried out have concluded that an expert system designed to be able to diagnose fungal plant diseases, the method used can be used as an alternative in calculating the diagnosis of fungal diseases and an expert system designed to make it easier for farmers to diagnose diseases that occur in fungal.